2015
DOI: 10.14712/18059694.2015.101
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis Dissecans of the Knee in Children and Adolescents: Our Experience with Transchondral Drilling

Abstract: Summary:Osteochondritis dissecans(OCD) of the knee is identified with increasing frequency in the adolescent patient. Left untreated, OCD can cause significant impairment and restriction in physical activity and development of osteoarthritis at an early age. The diagnosis of lesions of OCD can be confirmed on plain radiographs. MRI has emerged as the gold standard to evaluate the stability of the lesion and the integrity of the overlying articular cartilage. Treatment of OCD lesions depend on the stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Based on the obtained results, they concluded that when (18). In another study, Shaikh et al evaluated 17 cases of juvenile OCD of the femoral condyle of the knee treated by transarticular drilling approach; they reported that in the case where conservative treatments do not result in any signs of healing or where the lesion is not stable, the lesion can be treated surgically, either just drilling or fixation accompanied by drilling to increase the level of healing (19). Chiang et al reported the treatment outcome of multiple drilling in a 20-year-old male with a massive OCD lesion at the lateral femoral condyle, accompanied by a non-complete type discoid meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the obtained results, they concluded that when (18). In another study, Shaikh et al evaluated 17 cases of juvenile OCD of the femoral condyle of the knee treated by transarticular drilling approach; they reported that in the case where conservative treatments do not result in any signs of healing or where the lesion is not stable, the lesion can be treated surgically, either just drilling or fixation accompanied by drilling to increase the level of healing (19). Chiang et al reported the treatment outcome of multiple drilling in a 20-year-old male with a massive OCD lesion at the lateral femoral condyle, accompanied by a non-complete type discoid meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…В некоторых исследованиях у детей с открытыми зонами роста отмечена полная регенерация в области очага 95-100 % [13,19,21]. Сравнение результатов транс-и ретроартикулярной туннелизации не выявляет преимуществ той или иной методики [49].…”
Section: аннотацияunclassified
“…Необходимо отметить, что данный метод лечения в настоящее время является самым распространенным при лечении пациентов с рассекающим остеохондритом I-II стадии (стабильный костный фрагмент) у детей и может быть применен при площади поражения не более чем 2,5 см 2 [13,21,22,48,49]. Эффективность репаративных методов лечения при болезни Кенига подтверждается рядом разноплановых актуальных публикаций как аналитическими обзорами, так и клиническими исследованиями [1, 4, 6-9, 13-17, 19-22, 40, 49-53].…”
Section: аннотацияunclassified